The occurrence of haemosporidian parasites in the Fennoscandian bluethroat (Luscinia svecica) population - Hellgren, Olof (Journal of Ornithology, 2005)
A total of 86 adult bluethroats (Luscinia svecica) from nine different localities, covering the full length of the Fennoscandian mountain range, were screened for blood parasites of the three genera Haemoproteus, Plasmodium and Leucocytozoon using a recently developed polymerase chain reaction method. The overall occurrence of infection was 59.3%. Prevalence of Leucocytozoon spp. (47.7%), Plasmodium spp. (23.3%) and Haemoproteus spp. (1.2%) was detected. Of the infected birds, 15.1% carried mixed infections. Five different mitochondrial DNA-lineages of Leucocytozoon spp., eight lineages of Plasmodium spp. and one lineage of Haemoproteus spp. were found. Due to large sequence divergence these corresponded to at least five different species, but with the possibility of all 14 being independent evolutionary units with the potential of evolving different effects on the host. Of the lineages of Leucocytozoon spp., the most common was found throughout the range. The occurrence of the second most common lineage of Leucocytozoon spp. showed significant variation in prevalence between sites. The data also showed molecular evidence of one lineage of Leucocytozoon sp. existing in more than one species of avian host, thus challenging the use of host taxon as a taxonomic character when distinguishing between different species leucocytozoids.